2019
DOI: 10.1002/er.5010
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of piezoelectric vibration energy harvesting with auxetic boosters

Abstract: This paper proposes a new concept to enhance the efficiency of the vibration energy harvesting via an intermediate booster. The boosters have auxetic struc-tures and exert extra stretching strain in two perpendicular directions. The concept is tested on a conventional cantilever beam under the base excitation. The problem consists of a cantilever beam subjected to a body load at low frequencies. An auxetic substrate is bonded to the beam with a thin epoxy layer, and the piezoelectric (PZT) element is attached … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Exploring the auxetic feature in energy harvesting is a relatively new (since 2017) line of research [40][41][42][43] . PZT buzzers are available, universal and low-price elements which are widely used for different functions.…”
Section: Results Of This Study Can Open a New Path To Application Of mentioning
confidence: 99%
“…Exploring the auxetic feature in energy harvesting is a relatively new (since 2017) line of research [40][41][42][43] . PZT buzzers are available, universal and low-price elements which are widely used for different functions.…”
Section: Results Of This Study Can Open a New Path To Application Of mentioning
confidence: 99%
“…Simulation results indicated that the ACBEH could produce up to 2.51 times the power generated by plain cantilever energy beam harvesters [149]. Auxetic structures are also being used in intermediate boosters to enhance the energy absorption capacity of conventional cantilever beam energy harvesters [150].…”
Section: Sensors and Actuatorsmentioning
confidence: 99%
“…Utilising the piezoelectric effect of materials, piezoelectric energy harvesting technology can capture the surrounding mechanical energy and convert it into electrical energy 3 . Compared to other energy harvesting methods, it offers advantages such as simple structure and energy density, which has resulted in it garnering attention in the research field in terms of realising road energy harvesting technologies 4 . Common piezoelectric materials used in energy harvesting are lead zirconate titanate (PZT) and polyethylene xylene sulphide (PVDF) 5 .…”
Section: Introductionmentioning
confidence: 99%
“…3 Compared to other energy harvesting methods, it offers advantages such as simple structure and energy density, which has resulted in it garnering attention in the research field in terms of realising road energy harvesting technologies. 4 Common piezoelectric materials used in energy harvesting are lead zirconate titanate (PZT) and polyethylene xylene sulphide (PVDF). 5 Typical transducer structures include Multilayer, Cymbal, Moonie, Stack, Bridge, and macrofiber composite.…”
Section: Introductionmentioning
confidence: 99%